2017
DOI: 10.1249/mss.0000000000001244
|View full text |Cite
|
Sign up to set email alerts
|

Skin Tattoos Alter Sweat Rate and Na+ Concentration

Abstract: Tattooed skin generated less sweat and a higher Na concentration than nontattooed skin when stimulated by pilocarpine iontophoresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 11 publications
1
31
1
Order By: Relevance
“…Discrepancies between methods of sweat stimulation can confound interpretation of studies investigating the impact of various host or external factors on sweat electrolyte concentrations. For example, one study found lower local sweating rates and a higher sweat [Na + ] on tattooed skin than contralateral non-tattooed skin when stimulated by pilocarpine iontophoresis (Luetkemeier et al 2017). However, in another study, skin tattoos did not alter local sweating rate or sweat [Na + ] of exercise-induced sweating (Rogers et al 2019).…”
Section: Sodium Chloride and Other Micronutrientsmentioning
confidence: 96%
“…Discrepancies between methods of sweat stimulation can confound interpretation of studies investigating the impact of various host or external factors on sweat electrolyte concentrations. For example, one study found lower local sweating rates and a higher sweat [Na + ] on tattooed skin than contralateral non-tattooed skin when stimulated by pilocarpine iontophoresis (Luetkemeier et al 2017). However, in another study, skin tattoos did not alter local sweating rate or sweat [Na + ] of exercise-induced sweating (Rogers et al 2019).…”
Section: Sodium Chloride and Other Micronutrientsmentioning
confidence: 96%
“…Limited data on sweat composition. Tattoos Chronic Reduced sweating rate and higher sweat [Na] in response to pharmacologically-induced local sweating than non-tattooed skin; unknown etiology [466][467][468]. More research involving exercise or heatinduced whole body sweating is needed.…”
Section: Secondary Hyperhidrosis Chronic/ Episodicmentioning
confidence: 99%
“…It has been seen that well-trained athletes "sweat more but swear better," that is, they Sports Nutrition and Performance DOI: http://dx.doi.org /10.5772/intechopen.84467 sweat more water, but the loss of electrolytes is lower [41]. Recent studies have compared both the rate of sweating and the concentration of sodium in tattooed people versus non-tattooed people, concluding that the most tattooed skin presented lower sweating rate and higher sodium concentration [42].…”
Section: Hydrationmentioning
confidence: 99%